2021
DOI: 10.21704/pja.v5i1.1656
|View full text |Cite
|
Sign up to set email alerts
|

Genetic behavior for seed yield and yield components in sesame (Sesamum indicum L.) under normal irrigation and water stress conditions

Abstract: Genetic behavior for seed yield and yield components in sesame (Sesamum indicum L.)under normal irrigation and water stress conditions Comportamiento genético del rendimiento de semillas y componentes del rendimiento en sésamo (Sesamum indicum L.) en condiciones normales de riego y estrés hídrico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
6
2
0
Order By: Relevance
“…of primary branches per plant, capsule length (cm) and 1000 seed weight (g) indicating the presence of an excess of dominant alleles than recessive alleles. The present findings are in accordance with those of Sedeck and Shafie (2013) [23] , Vekaria et al (2015) [27] , El-Kadar et al (2017) [6] and Ibrahim et al (2021) [12] for seed yield per plant and one or more components in sesame. The information of number of gene/group of gene responsible for particular trait is vital for the genetic progress through selection.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…of primary branches per plant, capsule length (cm) and 1000 seed weight (g) indicating the presence of an excess of dominant alleles than recessive alleles. The present findings are in accordance with those of Sedeck and Shafie (2013) [23] , Vekaria et al (2015) [27] , El-Kadar et al (2017) [6] and Ibrahim et al (2021) [12] for seed yield per plant and one or more components in sesame. The information of number of gene/group of gene responsible for particular trait is vital for the genetic progress through selection.…”
Section: Resultssupporting
confidence: 93%
“…The value of H1 was greater than H 2 for all the traits (Table 2) indicating that the frequency of gene distribution in the parental lines was unequal and this was also proved by the ratio of H 2 /4H 1 (< 0.25) which confirmed the unbalanced distribution of gene at the loci in the parents implying dominance for all the traits. The results are in accordance with Sedeck and Shafie (2013) [23] , Vekaria et al (2015) [27] and Ibrahim et al (2021) [12] . Mather and Jinks (1971) [19] , while discussing the short comings of numerical component analysis suggested that (H 1 /D)0.5 at each locus is true for major degree of dominance only, where the distribution of dominance and recessive genes is symmetrical.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations